Cross-sectional structure-property relationship in a graded nanocrystalline Ti1−xAlxN thin film. (1st January 2016) - Zalesak, J.; Bartosik, M.; Daniel, R.; Mitterer, C.; Krywka, C.; Kiener, D.; Mayrhofer, P.H.; Keckes, J.
Abstract: The influence of simultaneously occurring gradients of crystalline phases, microstructure, chemical composition and strains on overall as well as local mechanical properties of nanocrystalline thin films is challenging to understand. In this work, cross-sectional structure-property relationships in a graded nanocrystalline 2 μm thick Ti1−x Alx N film were analyzed using in-situ bending tests on micro-cantilevers in transmission electron microscope, synchrotron X-ray nanodiffraction and nanoindentation. The results document that sub-micron depth variations of fracture stresses, hardness and elastic moduli depend on phases, crystallite sizes, crystallographic texture, Ti/Al ratio and residual strain. The local mechanical properties are primarily influenced by cross-sectional occurrence of binary and ternary phases and their intrinsic properties. Secondly, the hardness and fracture stress gradients depend on cross-sectional microstructure, especially on the local crystallite sizes and shapes as well as fiber textures. Two nucleation regions of cubic TiN and hexagonal Ti1−x Alx N phases with globular shaped crystal sizes in the nm range and relatively large in-plane residuals strains result in significantly higher hardness and fracture stresses in comparison with a coarse-grained region consisting of columnar cubic Ti1−x Alx N crystallites. The fracture behavior of cantilevers with ∼0.5 × 0.5 μm 2 cross-section depends also on the apparent grain size whereby the nucleation regions exhibit linear-elastic fracture in contrast to partly ductile response of the region with elongated nanocrystals. Finally, the experimental data indicate the possibility of mechanical optimization of nanocrystalline thin films through cross-sectional nanoscale design. Graphical abstract: